2021
DOI: 10.3390/jcm10071512
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Multidisciplinary Intervention for Health Promotion in the Workplace: A Pilot Study

Abstract: The aim of this study was to assess the effects of a joint health promotion intervention on a cohort of healthcare workers (HCWs) who had at least one cardiovascular risk factor. The HCWs were assessed at three different times, i.e., time zero (T0), after 6 months (T6), and after 12 months (T12). The following parameters were measured at a medical examination: physical activity, blood pressure, waist circumference, body mass index (BMI), routine laboratory tests, plicometric analysis, work ability index (WAI),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 58 publications
1
22
0
3
Order By: Relevance
“…The results of our study reported an increase in sedentary time among home workers; it is well known that an increase in sedentary behaviors is among the most important public health factors due to their unfavorable physical and mental health impacts [ 29 , 30 , 31 , 32 ]. Employers should preserve employees’ health, thus increasing work productivity and preventing sick days [ 33 ].…”
Section: Discussionmentioning
confidence: 62%
“…The results of our study reported an increase in sedentary time among home workers; it is well known that an increase in sedentary behaviors is among the most important public health factors due to their unfavorable physical and mental health impacts [ 29 , 30 , 31 , 32 ]. Employers should preserve employees’ health, thus increasing work productivity and preventing sick days [ 33 ].…”
Section: Discussionmentioning
confidence: 62%
“…Planning such interventions may be difficult, given the heavy workloads of healthcare workers. Effective interventions should also address work organization (e.g., the distribution of night shifts and the rotation in multiple settings with different workloads) and include occupational physicians’ role in promoting healthy habits, which are effective in preserving good health status and work ability [ 49 ]. Furthermore, other needed interventions are those which can improve relationships between colleagues.…”
Section: Discussionmentioning
confidence: 99%
“…Conscious actions and engagement of the employee towards the prevention of involutionary processes combined with the employer’s policy in that respect may effectively lead to a change of lifestyle into a healthier one and to the improvement of work efficiency [ 8 ].…”
Section: Introductionmentioning
confidence: 99%